The Role of Organizational Culture on Innovative Behaviour Mediated by Knowledge Transfer and Moderated by Work Autonomy at Regional Disaster Management Agency (BPBD) of Yogyakarta Special Region Province (DIY) - Jayanto, Nur Dwi; Effendi, M. Irhas; Religia, Yoga (Multidiscience : Journal of Multidisciplinary Science, 2025)
This study examines the impact of Organizational Culture (OC) on Innovative Behaviour (IB), with Knowledge Transfer (KT) as a mediator and Work Autonomy (WA) as a moderator at the Regional Disaster Management Agency (BPBD) of Yogyakarta Special Region. A quantitative approach using a census method was applied, encompassing all 111 employees, including 38 Civil Servants (PNS) and 73 Contract-based Employees (PPPK). Data were collected through structured questionnaires and analyzed using Partial Least Squares (PLS) with SmartPLS 3. Findings reveal that OC influences IB directly and through KT, while KT positively affects IB but does not mediate the OC-IB relationship effectively. This indicates a more substantial direct effect of OC on IB. Additionally, WA directly enhances IB but does not moderate the KT-IB relationship. The study underscores the importance of an OC characterized by openness, collaboration, tolerance for failure, and managerial support in fostering innovation. Practical implications suggest enhancing OC, leveraging technology-based KT systems, and promoting work autonomy policies to boost employee creativity. These findings offer strategic insights for improving innovation and efficiency in public sector organizations.